Clinical characteristics, treatment patterns and healthcare resource utilisation for portopulmonary hypertension patients in the USA: a real-world study - Hilary Dubrock; Julia Harley; Mark Small; Megan Scott; Peter Agron; Yuen Tsang; Sumeet Panjabi (BMJ Open)
Objectives To investigate demographic, clinical characteristics, treatment patterns and healthcare resource utilisation (HCRU) among patients with portopulmonary hypertension (PoPH).Design Retrospective analysis of a real-world cross-sectional survey, the pulmonary arterial hypertension (PAH) Disease Specific Programme.Setting Secondary care settings in the USA.Participants Pulmonologists (n=22), cardiologists (n=17) and internists (n=7) who saw ≥2 patients with PAH/month provided data on 90 PoPH patients. Mean age of patients was 56.8 years, 51.1% were male, 76.7% were white/Caucasian.Primary and secondary outcome measures Demographic characteristics, initial presentation/diagnosis, disease trajectory, symptoms, comorbidities, treatment patterns and HCRU.Results The most common diagnostic tests were echocardiogram (62.2%), right heart catheterisation (56.7%) and electrocardiogram (48.9%). Dyspnea on exertion (64.4%), dyspnea following exertion (51.1%) and fatigue (48.9%) were the most common symptoms prior to PAH diagnosis as well as the most bothersome. Overall, 13.3% patients had mild disease before treatment vs 42.2% at time of survey. Most (60.0%) had stable disease (21.1% were improving and 18.8% were deteriorating at the time of the survey). Most common recent symptoms were dyspnea on exertion (51.1%), fatigue (37.8%) and dyspnea following exertion (32.2%). Patients had a mean of 1.8 comorbidities. In total, 80.0% of PoPH patients were receiving PAH-specific treatment; 41.7%, 22.2% and 12.5% received monotherapy, dual therapy and triple therapy, respectively. Patients had seen their physician 4.1 times in the past 12 months (3.5 visits specifically for PAH), while 31.1% had been hospitalised for PAH. Most (70.0%) patients were managed in a multidisciplinary team, and 8.9% of patients relied on a caregiver.Conclusions This study highlights the high symptomatic burden coupled with mostly moderate-to-severe disease status and a high hospitalisation rate despite the majority of PoPH patients being on therapy. Therefore, new treatment options in PoPH are in great need.